Pengembangan Bahan Ajar Interaktif Berbasis Website Pada Topik Larutan Elektrolit dan Non Elektrolit - Fanny Fashiri; Nora Susanti (Jurnal Inovasi Pembelajaran Kimia (Journal Of Innovation in Chemistry Education), 2020)
This study aims to know the feasibility of an interactive learning material based on a website that innovated based on BSNP. The research method used Research and Development (R&D) with the ADDIE models which consist of five stages are analysis, design, development, implementation, and evaluation. Data collected technique used for feasibility was a questionnaire of BSNP was given to experts lecture. The analysis results of this research are the interactive learning material based on the website was feasible that used questionnaire of BSNP showed a score of the truth, breadth, and depth of concept aspects was 4.66, material and question device aspects was 4.56, language structure aspects was 5.0, display of media aspects was 4.83, software engineering aspects was 4.33, usefulness aspects was 4.66. The average score overall validation of interactive learning material based on the website on the electrolyte and nonelectrolyte solution topic was 4.67. The average score overall validation of interactive learning material based on the website on the electrolyte and nonelectrolyte solution topic shows that this media is very eligible and can be used in the learning process.